On the variational homotopy perturbation method for nonlinear oscillators - Fernández, Francisco M. (Universidad Nacional de La Plata) (2012)
In this paper, I discuss a recent application of a variational homotopy perturbation method to rather simple nonlinear oscillators. It is shown that the main equations are inconsistent and for that reason the results may be of scarce utility.